A condition-based maintenance policy with non-periodic inspection for k-out-of-n: G systems - Liu, Yongchao; Wang, Guanjun; Liu, Peng (Reliability engineering & system safety, 2024)
This paper studies a condition-based maintenance policy for k-out-of-n: G systems subject to economic dependence. All components in the system are identical and unrepairable, with an exponential lifetime distribution. The state of the system is not self-announcing, which can only be revealed by inspection. At each inspection moment, the maintenance decision and the next inspection plan are made according to the system status revealed by the inspection. The optimal maintenance strategy can be obtained in three steps. Firstly, a dynamic programming approach is used to determine the sequence of optimal inspection intervals gradually. Secondly, a searching method is used to optimize the preventive maintenance threshold of the system based on the renewal process theory. Thirdly, the optimal number of components that constitutes the redundant system is decided. Furthermore, the average availability and mean time to failure of the system are also derived iteratively. The effectiveness of the proposed maintenance policy is validated by a 5-out-of-n: G system. Numerical comparison with the periodic inspection policy shows the outstanding performance of the proposed maintenance policy. •A condition-based maintenance policy for k-out-of-n: G systems is studied.•Non-periodic inspection intervals are determined by using dynamic programming method.•Unit number n and PM threshold r are optimized by minimizing the average cost rate.•Average availability and the mean time to failure of the system are obtained.•Numerical comparisons between periodic and non-periodic inspections are conducted.